Comparative study on welding energy and Interface characteristics of titanium‑aluminum explosive composites with and without interlayer. (1st January 2021) - Wu, Xiaoming; Shi, Changgen; Fang, Zhonghang; Lin, Sunlang; Sun, Zerui
Abstract: In order to obtain titanium and aluminum composites with excellent performance and master the energy flow form when interlayer is used in explosive welding technology, energy calculation, SPH numerical simulation and experiment were used to conduct a comparative study of TA2/5083 and TA2/1060/5083 in this paper. Under the experiment conditions, TA2/1060, 1060/5083, TA2/5083 interface welding energy are respectively 547.17 MJ, 1178.86 MJ and 1455.5 MJ.The use of 1060 interlayer improves energy utilization efficiency by 14%. Numerical simulations and experiments showed that there was a continuous melting zone and a non-welded zone at the interface without interlayer. After the interlayer was used, the TA2/1060 interface was flat and the 1060/5083 interface showed a wave. There was no brittle intermetallic compound at the titanium‑aluminum composite interface. The use of interlayer reduces the welding energy of a single interface, and the constructed theoretical equation showed that the interface energy can be accurately designed by adjusting parameters of explosives, flyer plates, interlayers and base plates. The use of pure aluminum interlayer is an effective means to improve titanium‑aluminum explosive welding conditions Graphical abstract: Unlabelled Image Highlights: A direct calculation formula for the welding energy of explosive welding interface is constructed. The use of interlayers to redistribute energy will definitely increase the energy utilization efficiency in any material，experiments improved by 14%. The prepared TA2/1060/5083 interface elements exist in the form of titanium‑aluminum solid solution, and there is no continuous melting zone. Pure aluminum can be used for explosive welding to prepare titanium alloy‑magnesium aluminum alloy composite materials.